1987
DOI: 10.1111/j.1432-1033.1987.tb10533.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a yeast mutant defective in cholinephosphotransferase

Abstract: A yeast mutant defective in cholinephosphotransferase (cpt) was isolated as a revertant from a choline-sensitive mutant, which exhibited lowered phosphatidylinositol synthesis. A block at the cholinephosphotransferase step in the mutant was indicated by the enzyme defect and the accumulation of CDP-choline in the cells with a decrease in phosphatidylcholine synthesis. The defect was due to a single recessive mutation in a nuclear gene. The residual activity in the mutant showed an increased apparent K, for CDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…EPT activity was purified 6-fold with 60% recovery, indicating that the latter activity remained relatively stable in the course of the solubilization-purification process. A number of reports had previously indicated that EPT, which is an enzyme distinct from CPT (25)(26)(27)(28), is much more stable than CPT in the presence of various detergents, including DOC (14,(29)(30)(31).…”
Section: Effect Of Detergents On Cpt Activity In Rat Ever Microsomesmentioning
confidence: 99%
“…EPT activity was purified 6-fold with 60% recovery, indicating that the latter activity remained relatively stable in the course of the solubilization-purification process. A number of reports had previously indicated that EPT, which is an enzyme distinct from CPT (25)(26)(27)(28), is much more stable than CPT in the presence of various detergents, including DOC (14,(29)(30)(31).…”
Section: Effect Of Detergents On Cpt Activity In Rat Ever Microsomesmentioning
confidence: 99%
“…Mutants defective only in the choline kinase gene (CKI) do not show any apparent growth phenotype [6], and are thus not suitable for ¢omplementation cloning. We introduced cki into the pss background to construct a cki pss double mutant.…”
Section: Ciotffng Strategymentioning
confidence: 99%
“…DNA encoding choline kinase has been isolated from two sources, yeast and rat liver, in our laboratory [3,4]. The yeast gene was obtained by complementation of the choline kinase mutation, cki [5,6], and rat liver choline kinase eDNA was recently cloned, using specific antibodies, from a 2gtl I rat liver eDNA library. The open reading frames in the yeast and rat liver clones encoded 582 and 435 amino acid residues with relative molecular masses of 66,316 and 49,737, respectively.…”
Section: Introductionmentioning
confidence: 99%